Jadar Project in light of critical raw materials supply - Jovović, Aleksandar (Napredak, 2024)
The paper provides an analysis of the global growth in demand for critical raw materials in terms of increasing demands for faster and greater use of renewable energy sources. The paper presents the most important European regulations, initiatives and projects. It also describes the basic characteristics of the Jadar Project, technical solutions, potential impacts and measures to reduce these impacts. Special attention is paid to emissions into air and water, as well as the method of disposal of industrial waste. All technical solutions are designed in accordance with the best available techniques, described in EU reference documents.